Acupuncture with twirling reinforcing and reducing manipulation shows a control of hypertension and regulation of blood pressure-related target brain regions in spontaneously hypertensive rat: a preliminary resting-state functional MRI study - Li, Yin-Yin; Liu, Ji-Peng; Shi, Shu-Feng; Yang, Ke-Zhen; Gong, Yu; Sun, Jiao; Xie, Qi; Wu, Xiao-Li; Liu, Qing-Guo; Xu, Meng (Frontiers in Neuroscience, 2023)
Aim To observe the effects of acupuncture manipulations on blood pressure and brain function in spontaneously hypertensive rats and elucidate the anti-hypertensive effect of the manipulations’ central mechanism. Methods This study used acupuncture twirling reinforcing, acupuncture twirling reducing, and acupuncture twirling uniform reinforcing-reducing manipulations to act on the bilateral TaiChong point of rats. The depth of acupuncture was 1.5–2 mm, and twisting was performed at a frequency of 60 times/min within ±360° for 3 min, followed by the needle being retained for 17 min. Functional magnetic resonance imaging was performed at the end of the intervention. Regional homogeneity and amplitude of low-frequency fluctuations were used to assess the differences in brain regions in each group of rats, and the core brain region (left hypothalamus) among the differential brain regions was selected as the seed for functional connectivity analysis. Results (1) The anti-hypertensive effect was achieved by acupuncture manipulations, and the anti-hypertensive effect of twirling reducing manipulation on spontaneously hypertensive rats was better than that of twirling uniform reinforcing-reducing and twirling reinforcing manipulations. (2) After regional homogeneity and amplitude of low-frequency fluctuations analyses, the hypothalamus, the brain region related to blood pressure, was activated in the twirling uniform reinforcing-reducing manipulation group; the corpus callosum and cerebellum were activated in the twirling reinforcing manipulation group; and the hypothalamus, olfactory bulb, corpus callosum, brainstem, globus pallidum, and striatum were activated in the twirling reducing manipulation group. (3) According to the functional connectivity analysis, different acupuncture manipulations increased the functional connections between seed points and the brainstem, olfactory bulb, and cerebellum, etc. Conclusion These results suggest that acupuncture manipulations achieved the hypotensive effect and the twirling reducing manipulation had a better hypotensive effect on spontaneously hypertensive rats than twirling uniform reinforcing-reducing and twirling reinforcing manipulations; the central mechanism of the anti-hypertensive effect of twirling reinforcing and reducing manipulation may be related to the activation of brain regions associated with blood pressure regulation and the functional connections between them. Furthermore, brain regions involved in motor control, cognition, and hearing were also activated. We hypothesize that activation of these brain regions may help prevent or mitigate the onset and progression of hypertensive brain damage.